Effect of Phototherapy on Serum Electrolyte Levels - Akpınar Gözetici, Melis; Kızılelma Yiğit, Avidan; Beşer, Ömer Faruk (Cerrahpaşa Medical Journal, 2021)
Objective: This study aimed to investigate the effect of phototherapy on serum electrolyte levels in neonates admitted to neonatal intensive care unit with the diagnosis of neonatal hyperbilirubinemia. Methods: Demographic profiles, laboratory findings, and electrolyte levels before phototherapy and 48-72 hours after phototherapy of 260 patients hospitalized with neonatal hyperbilirubinemia between June 2016 and June 2018 were compared in this retrospective study. Results: The mean sodium level significantly decreased from 140.5 mg/dL to 139.1 mg/dL after phototherapy. The decrease in potassium level was not statistically significant. The mean calcium level significantly decreased from 9.98 mg/dL to 9.55 mg/dL. The mean chloride level before phototherapy significantly decreased from 106.4 mmol/L to 105.9 mmol/L after phototherapy. Conclusion: The level of serum electrolytes in newborns may change with phototherapy. Serum sodium, chloride, and calcium levels may decrease after phototherapy. For prevention of possible adverse effects, the changes in electrolyte levels should be considered in the clinical course of newborns receiving phototherapy and appropriate fluid-electrolyte treatments should be given. Cite this article as: Akpınar Gözetici M, Kızılelma Yiğit A, Beşer ÖF. Effect of Phototherapy on Serum Electrolyte Levels. Cerrahpaşa Med J 2021; 45(1): 16-20.